2018
DOI: 10.2967/jnumed.117.205203
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Quantitative SPECT/CT for Evaluation of Lung Shunt Fraction Before SIRT of Liver Tumors

Abstract: The lung shunt fraction (LSF) is estimated using Tc-macroaggregated albumin (Tc-MAA) imaging before selective internal radiotherapy (SIRT) of the liver to reduce the risk of pulmonary irradiation. Generally, planar scans are acquired after injection of Tc-MAA into the hepatic artery. However, the validity of this approach is limited by differences in attenuation between liver and lung tissue as well as inaccurate segmentation of the organs. The aim of this study was to evaluate quantitative SPECT/CT for LSF as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 27 publications
5
48
0
1
Order By: Relevance
“…The derived uncertainties in LSF and LMD for our methodology were 10% and 13%, respectively. We found that both LSF new and LMD new were significantly lower than the values estimated using the microsphere package‐insert instructions, which is consistent with previous publications . LSF new and LMD new were always lower than the planar scintigraphy‐based values, with an average difference of −0.05 Gy (−63%) and −5 Gy (−53%), respectively.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The derived uncertainties in LSF and LMD for our methodology were 10% and 13%, respectively. We found that both LSF new and LMD new were significantly lower than the values estimated using the microsphere package‐insert instructions, which is consistent with previous publications . LSF new and LMD new were always lower than the planar scintigraphy‐based values, with an average difference of −0.05 Gy (−63%) and −5 Gy (−53%), respectively.…”
Section: Discussionsupporting
confidence: 90%
“…In our methodology, total lung mass was estimated from diagnostic chest CT contours drawn using a well‐established lung region‐growing algorithm . Previous studies of 90 Y‐microsphere lung dosimetry have used upper HU thresholds ranging from −150 to −600 HU to derive the lung contours . Our empirically calculated upper HU thresholds of −280 HU for CT maa and −340 HU for CT diag fall within the range of these previous reports.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations